Utilization Of Construction And Demolition Waster And Environmental Management Practice In South East Asian Countries - Hui Yee Ngieng; Tony Hadibarata; Rubiyatno (Tecno Scientifica Publishing, 2021)
The ASEAN population will increase to 724.8 million by the year 2030 and the urbanization rate increases with years. This leads to the development of the construction industry to fulfil the fundamental social and physical requirements. Construction activities create an adverse negative impact on the environment, such as pollution and damage to the environment. This article will study more about the construction and demolition waste (C&D waste) and it can be founded in various construction stages. Therefore, the government and authorities introduce environmental management practices to mitigate the negative impact on construction on the environment and minimize the pollution at the source. What, why and where are terms required to consider before the implementation of environmental management practice. The government policies of Malaysia, Singapore and Thailand are summarized. Approximately 10% of total synthetic carbon dioxide (CO2) sourced from concrete production. The content more emphasizes the green materials generated from agricultural waste to replace the silica in concrete. The bamboo is used as interior decoration and material for building construction. Green materials technology is solar panel, solar thermal collector, geothermal technology, hydropower technology and cooling roof system.